2017
DOI: 10.1186/s12939-017-0517-y
|View full text |Cite
|
Sign up to set email alerts
|

Does equity in healthcare spending exist among Indian states? Explaining regional variations from national sample survey data

Abstract: BackgroundEquity and justice in healthcare payment form an integral part of health policy and planning. In the majority of low and middle-income countries (LMICs), healthcare inequalities are further aggravated by Out of Pocket Expenditure (OOPE). This paper examines the pattern of health equity and regional disparities in healthcare spending among Indian states by applying Andersen’s behavioural model of healthcare utilization.MethodsThe present study uses data from the 66th quinquennial round of Consumer Exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
72
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(74 citation statements)
references
References 40 publications
2
72
0
Order By: Relevance
“…A recent study used a composite index of socioeconomic development of states based on their per-capita income, average educational attainment and fertility rates, and found it to be inversely related to epidemiological transition ratio, with a correlation coefficient of -1.81 in 2016 [ 22 ]. The wealthier states spend more on health care, offer more extensive provision of private health care services [ 41 – 43 ], and their residents also have relatively more resources to invest in health [ 44 ] which often results in higher CHE in the absence of adequate risk pooling mechanism. Projection of CHE till 2040 in 179 countries found that if future expansion of health services availability is more rapid than the shift towards prepayments, CHE may increase with economic growth [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study used a composite index of socioeconomic development of states based on their per-capita income, average educational attainment and fertility rates, and found it to be inversely related to epidemiological transition ratio, with a correlation coefficient of -1.81 in 2016 [ 22 ]. The wealthier states spend more on health care, offer more extensive provision of private health care services [ 41 – 43 ], and their residents also have relatively more resources to invest in health [ 44 ] which often results in higher CHE in the absence of adequate risk pooling mechanism. Projection of CHE till 2040 in 179 countries found that if future expansion of health services availability is more rapid than the shift towards prepayments, CHE may increase with economic growth [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…The study found that people residing in urban areas, having higher economic status, belonging to non-Muslim communities, non-scheduled tribes (STs), and non-poor HHs spend more on healthcare than their counterparts. [ 5 ]…”
Section: Introductionmentioning
confidence: 99%
“…Healthcare governance and ethics should be moral imperatives for anyone working in the healthcare environment, including policymakers, administrators and healthcare leaders. For instance, low-middle income countries such as India, have fragmented healthcare systems, and policy initiatives can fail for any number of reasons, including chronic underfunding, weak systems of governance and ethical codes that are not upheld and do not translate into practice [6,7]. However, this need not be the case and it should be possible to adopt a multi-lateral approach to healthcare regulation and governance, building systems for vertical and horizontal integration into local leadership frameworks.…”
Section: Discussionmentioning
confidence: 99%